2005
DOI: 10.1111/j.1365-2788.2005.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of behaviour problems on caregiver stress in young people with autism spectrum disorders

Abstract: Results of this study suggested that it is a specific group of externalized behaviours that are the most strongly associated with both parent and teacher stress. Results were discussed from methodological and conceptual perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
629
5
31

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 935 publications
(724 citation statements)
references
References 37 publications
(44 reference statements)
59
629
5
31
Order By: Relevance
“…The challenging behaviors of children with ASD have been repeatedly associated with poor maternal psychological well-being Allik, Larsson, & Smedje, 2006;Herring et al, 2006) and high levels of stress (Bromley, Hare, Davison, & Emerson, 2004;Lecavalier, Leone, & Wiltz, 2006). There is some Correspondence concerning this article should be addressed to: Leann E. Smith, Waisman Center, University of Wisconsin-Madison, 1500 Highland Ave., Madison, WI 53705.…”
Section: Child Characteristics and Maternal Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenging behaviors of children with ASD have been repeatedly associated with poor maternal psychological well-being Allik, Larsson, & Smedje, 2006;Herring et al, 2006) and high levels of stress (Bromley, Hare, Davison, & Emerson, 2004;Lecavalier, Leone, & Wiltz, 2006). There is some Correspondence concerning this article should be addressed to: Leann E. Smith, Waisman Center, University of Wisconsin-Madison, 1500 Highland Ave., Madison, WI 53705.…”
Section: Child Characteristics and Maternal Well-beingmentioning
confidence: 99%
“…In a sample of children and adolescents with ASDs, Lecavalier and colleagues (2006) found that self-isolated/ritualistic behaviors were associated with poorer parent outcomes, controlling for externalizing behaviors, leading the researchers to posit that severity of the core features of autism may additionally contribute to caregiver stress (Lecavalier et al, 2006). In a study of preschool children with intellectual disabilities (autism, cerebral palsy, Down syndrome, and undifferentiated developmental delay), autism group status contributed significantly to mothers' reports of negative impact even after controlling for maternal education level, children's behavior problems, and cognitive level, suggesting that certain aspects of raising a child with autism, above and beyond behavior problems, negatively impact maternal stress (Eisenhower et al, 2005).…”
mentioning
confidence: 99%
“…Mental ill-health is recognised to have a negative impact on long term outcomes for individuals with autism and intellectual disabilities (Billstedt et al, 2005;Bradley et al, 2006). Furthermore, problem behaviours are associated with increased family (Lecavalier, Leone, & Wiltz, 2006), and carer stress (Tyrer et al, 2006), and in adults with autism and intellectual disabilities has a strong association with the risk of being moved to an out of area placement, and increased service costs (Allen, Lowe, Moore, & Brophy, 2007). Research is required to develop an understanding of the risk and vulnerability factors relevant to the development of mental illhealth in children, young people and adults with intellectual disabilities.…”
Section: Future Directionsmentioning
confidence: 99%
“…These responses take the form of irritability, poor anger control, temper tantrums, self-injurious behavior, aggression, and mood dysregulation (Lecavalier et al 2006;Prizant and Laurent 2011;Quek et al 2012). In addition, there is an increasing recognition of the impact of severe emotion disturbances in ASD (Laurent and Rubin 2004;Mazefsky et al 2012;Samson et al 2012), and initial empirical findings suggests that maladaptive emotional responses may contribute to impaired functioning (Jahromi et al 2013) and could consequently affect long-term outcome.…”
Section: Introductionmentioning
confidence: 99%